Analisis Validitas Konstrak dan Analisis Konsistensi Internal pada Skala Resiliensi - Prawita, Egi; Heryadi, Adi (PSIMPHONI, 2023)
Resilience, a core concept in positive psychology, plays a crucial role in individuals' ability to navigate and overcome challenges. It encompasses the capacity to adapt and recover from adversity while maintaining focus on personal goals. Key aspects of resilience include: (1) personal competence, high standards, and persistence; (2) reliance on one's instincts, tolerance of negative emotions, and the capacity to leverage stress constructively; (3) positive acceptance of change and secure interpersonal relationships; (4) self-control; and (5) spiritual influences. This study evaluates the construct validity and internal consistency of a resilience scale for adults in Indonesia using confirmatory factor analysis (CFA) and reliability testing. The results indicate that the scale is both reliable (α = 0.887) and valid, with a well-fitting CFA model. Future research should explore the scale's applicability across diverse cultural contexts and its potential for longitudinal studies to assess resilience over time. Additionally, investigating the scale's sensitivity to different life events could enhance its utility in practical settings.